Monitoring Upper Limb Recovery after Cervical Spinal Cord Injury: Insights beyond Assessment Scores - Brogioli, Michael; Schneider, Sophie; Popp, Werner L.; Albisser, Urs; Brust, Anne K.; Velstra, Inge-Marie; Gassert, Roger; Curt, Armin; Starkey, Michelle L. (Frontiers in Neurology, 2016)
Background: Pre-clinical investigations in animal models demonstrate that enhanced upper-limb (UL) activity during rehabilitation promotes motor recovery following spinal cord injury (SCI). Despite this, following SCI in humans, no commonly applied training protocols exist and therefore activity-based rehabilitative therapies (ABRT) vary in frequency, duration and intensity. Quantification of UL recovery is limited to subjective questionnaires or scattered measures of muscle function and movement tasks. Objective: To objectively measure changes in UL activity during acute SCI rehabilitation and to assess the value of wearable sensors as novel measurement tools that are complimentary to standard clinical assessments tools. Methods: The overall amount of UL activity and kinematics of wheeling were measured longitudinally with wearable sensors in 12 thoracic and 19 cervical acute SCI patients (complete and incomplete). The measurements were performed for up to seven consecutive days, and simultaneously, SCI-specific assessments were made during rehabilitation sessions one, three, and six months after injury. Changes in UL activity and function over time were analysed using linear mixed models. Results: During acute rehabilitation the overall amount of UL activity and the active distance wheeled significantly increased in tetraplegic patients, but remained constant in paraplegic patients. The same tendency was shown in clinical scores with the exception of those for independence, which showed improvements at the beginning of the rehabilitation period, even in paraplegic subjects. In the later stages of acute rehabilitation the quantity of UL activity in tetraplegic individuals matched that of their paraplegic counterparts despite their greater motor impairments. Both subject groups showed higher UL activity during therapy-time compared to the time outside of therapy time. Conclusion: Tracking day-to-day UL activity is necessary to gain insights into the real impact of a patient’s impairments on their UL movements during therapy as well as during their leisure time. In the future, this novel methodology may be used to reliably control and adjust ABRT, and to evaluate the progress of upper limb rehabilitation in clinical trials.